(untitled) (Journal of Plant Disease Sciences, 2023)
Mango leaf spot often caused by Colletotrichum gloeosporioides and Pestolotiopsis mangiferae which are very common in areas of wet and warm environments. Growers have become concerned about these pathogens because they have been known to harm fruits and leaves. One strategy for controlling diseases, particularly foliar pathogens, has been the use of chemical fungicides. This study assessed seven broad spectrum fungicides against two main fungi (C. gloeosporioides and P. mangiferae) that cause leaf spots in vitro using the poisoned food technique. Data revealed that the mycelial development of the test pathogen was successfully inhibited by all systemic fungicides tested (each at 500 and 1000 ppm) compared to the untreatedcontrol, andthat this effect wasdirectlycorrelatedwith concentrations. At both concentrations, carbendazim was found to be highly efficient in inhibiting mycelial growth against the tested pathogen.